Preparation method of maleic acid-acrylic acid copolymer

By using copper sulfate pentahydrate and ferrous sulfate heptahydrate to make a composite catalyst, and combining azo initiator and hydrogen peroxide to control the reaction conditions, the problem of large residual amount of initiator and free monomer in the prior art is solved, and the problem of large residual amount of initiator and free monomer in the prior art is achieved. Maleic acid-acrylic copolymers with low color and high dispersion properties were prepared.

CN119285836APending Publication Date: 2025-01-10JIYUAN QINGYUAN WATER TREATMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411682422.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing maleic acid-acrylic acid copolymer preparation method, the residual amount of persulfate and sulfite is large, which affects the addition effect of detergent additives. The presence of metal ions in another method causes the solution to have color, platinum and cobalt. High chromaticity affects application.

Method used

Copper sulfate pentahydrate and ferrous sulfate heptahydrate are used to make a composite catalyst, azo initiator and hydrogen peroxide are used as initiators, the reaction temperature and time are controlled, and the monomer is added dropwise, and the synergistic effect of the composite catalyst and azo initiator is carried out. , reduce free monomer and chromaticity.

Benefits of technology

It has achieved a small initiator residue, a small maleic acid free monomer residue, a low platinum-cobalt color, and no three wastes generated. The chelation and dispersion performance of the product is better than that of similar products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a maleic acid-acrylic acid copolymer, and belongs to the field of fine chemical engineering. The preparation method comprises the following steps: preparing a composite catalyst solution from copper sulfate pentahydrate and ferrous sulfate heptahydrate; a main initiator azo initiator aqueous solution and an auxiliary initiator hydrogen peroxide aqueous solution are adopted, and maleic acid and acrylic acid monomers are subjected to low-temperature polymerization to prepare a maleic acid-acrylic acid copolymer aqueous solution. The residue of maleic acid free monomer in the maleic acid-acrylic acid copolymer prepared by the method is not more than 30ppm, the platinum-cobalt chromaticity is not more than 100, and no three wastes are generated in the whole process. Meanwhile, the chelation dispersing performance of the maleic acid-acrylic acid copolymer is superior to that of similar products at home and abroad.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fine chemicals, and in particular relates to a method for preparing a maleic acid-acrylic acid copolymer. Background Art

[0002] Maleic acid-acrylic acid copolymer is a kind of chelated dispersed copolymer with excellent performance. Because the polymer contains carboxyl groups, it can dissociate hydrogen ions and polymer anions in aqueous solution. This anion is Ca 2+ , Fe 3+ It is an excellent chelating agent for cations such as chondroitin and d-Hydroxy- ...

[0003] Maleic acid-acrylic acid copolymer is a high molecular weight phosphorus-substituted detergent builder that can chelate Ca 2+ Mg 2+ It has the function of softening water and suspending dirt in water, thereby preventing inorganic salts from crystallizing on the surface of clothes and having anti-redeposition effect. Therefore, it can be widely used in industrial water treatment systems and detergent additives. At present, there are two commonly used preparation methods in China. One is to use persulfate as the initiator of the copolymer reaction and bisulfite as the chain regulator. This redox system is used for reaction. However, the disadvantage of this method is that the residual amount of persulfate and sulfite is large, which affects the addition of detergent additives in the later stage. The other method uses hydrogen peroxide as the initiator and metal ions as catalysts and regulators. This method has a large residual amount of maleic acid (MA) free monomer. Since metal ions are generally soluble in water and the solution has color, the platinum cobalt chroma is basically above 200, which has a certain impact on the later application. Therefore, a new polymerization method is needed to ensure a small amount of initiator residue, small chroma and small residual amount of MA free monomer. Summary of the invention

[0004] Based on the technical problems existing in the existing maleic acid-acrylic acid copolymer preparation method, the present invention provides a maleic acid-acrylic acid copolymer preparation method. The preparation method of the present invention can ensure a small amount of initiator residue, a small chromaticity and a small amount of MA free monomer residue.

[0005] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a maleic acid-acrylic acid copolymer comprises the following steps: Step (1), preparing a composite catalyst solution using copper sulfate pentahydrate and ferrous sulfate heptahydrate; Step (2), respectively preparing an aqueous solution of an azo initiator as a main initiator and an aqueous solution of hydrogen peroxide as a secondary initiator; Step (3), preparing a maleic acid aqueous solution, referred to as monomer a; preparing an acrylic acid aqueous solution, referred to as monomer b; Step (4), adding pure water into a four-necked flask, then adding the composite catalyst solution, introducing nitrogen protection, heating the water bath to 55°C, starting stirring, and then simultaneously adding the primary initiator, secondary initiator, monomer a, and monomer b dropwise, and controlling the temperature at 55°C-60°C during the process; Step (5), after the addition of monomer a is completed, the main initiator, the secondary initiator and the monomer b are continued to be added dropwise, the time is controlled within 1 hour, and the temperature is maintained at 55-60°C. After all the additions are completed, the temperature is kept for 0.5-1 hour, and the temperature is lowered to obtain the maleic acid-acrylic acid copolymer aqueous solution.

[0006] Furthermore, in the step (1), the mass fraction of copper sulfate in the composite catalyst solution is 1%-10%, and the mass fraction of ferrous sulfate is 1%-10%.

[0007] Furthermore, in step (1), the molar ratio of copper sulfate to ferrous sulfate in the composite catalyst is 0.25-2.

[0008] Furthermore, the main initiator azo initiator in step (2) is preferably a water-soluble azo initiator, specifically azobisisobutylamidine hydrochloride and / or azobisisobutylimidazoline hydrochloride. However, oil-soluble azo initiators or amphoteric azo initiators may also be selected, such as azobisisobutylonitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME), azoisobutylcyanamide (V30), and the like, but are not limited thereto.

[0009] As a specific implementation, when the main initiator azo initiator is a mixture of azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride, the mass ratio thereof is 0.25-1.

[0010] Furthermore, in step (2), the mass fraction of the main initiator azo initiator aqueous solution is 2%-25%, preferably 5%-20%.

[0011] Furthermore, the mass fraction of the secondary initiator hydrogen peroxide aqueous solution in step (2) is 25%.

[0012] Furthermore, in step (3), the aqueous maleic acid solution is prepared by adding a certain amount of water to solid maleic anhydride and hydrolyzing it into the aqueous maleic acid solution.

[0013] Furthermore, in step (5), the mass fraction of the acrylic acid aqueous solution is 90%-95%.

[0014] Furthermore, in step (5), the molar ratio of maleic acid: acrylic acid: composite catalyst: azo initiator: hydrogen peroxide is 1: 1.0-3.6: 0.001-0.0018: 0.001-0.008: 0.3-0.7.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Using azo as the main initiator can efficiently initiate free radicals at a lower temperature. Compared with inorganic persulfate and other water-soluble initiators, azo initiators can carry out smooth, stable and controllable decomposition reactions to produce highly linear and high molecular weight polymers.

[0016] 2. The addition time of acrylic acid monomer is extended relative to that of maleic acid monomer. If the extension time is controlled within 1 hour, it will help reduce the free monomers in the later stage.

[0017] 3. Catalysts use composite catalysts to improve the synergistic effect of catalysts, which helps to reduce free monomers in the later stage. The presence of iron ions and copper ions can improve the initiation efficiency of both azo initiators and hydrogen peroxide catalysts, and the rapid generation of free radicals can make monomers easier to copolymerize.

[0018] 4. The residual free monomer of maleic acid in the maleic acid-acrylic acid copolymer prepared by the present invention is not more than 30ppm (mass fraction is not more than 0.003wt%), the platinum-cobalt chromaticity is not more than 100, and no three wastes are generated in the whole process. At the same time, the chelating and dispersing properties of the maleic acid-acrylic acid copolymer are better than similar products at home and abroad. DETAILED DESCRIPTION

[0019] The technical solutions and effects of the present invention are further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1

[0020] The preparation method of the maleic acid-acrylic acid copolymer of this embodiment comprises the following steps: Step 1: Add 105g of pure water to a four-necked round-bottom flask, and mix copper sulfate pentahydrate and ferrous sulfate heptahydrate at a ratio of 0.0016 mol (molar ratio of Fe 2+ :Cu 2+ =1:1) was dissolved in 5g pure water to prepare a composite catalyst solution, which was then added to a four-necked flask; Step 2: Weigh 90g of maleic anhydride solid, add it to 192.6g of pure water, place in a water bath at 80°C, keep warm for 30 minutes, and after the hydrolysis is completed, cool to room temperature to prepare a maleic acid monomer solution; Step 3: Weigh 210 g of acrylic acid, add 20 g of pure water, and prepare an acrylic acid monomer solution; Step 4: Dissolve 1.5g VA-044 in 20g pure water to prepare the main initiator; Step 5: Weigh 50g of 25% hydrogen peroxide as a secondary initiator; Step 6: Start stirring, raise the temperature of the water bath to 55°C, and simultaneously add the primary initiator, secondary initiator, maleic acid monomer solution and acrylic acid monomer solution dropwise for 3 hours, maintain the reaction temperature at 55-60°C, and complete the addition of the maleic acid monomer solution; Step 7: Continue to drop the main initiator, secondary initiator and acrylic acid monomer solution and complete the dropwise addition within 1 hour; Step 8: After all the additions are completed, keep the temperature for 30 minutes, cool down to below 45°C, add 342.5 g of 50% by mass sodium hydroxide solution, and obtain a maleic acid-acrylic acid copolymer solution with a mass fraction of about 40%.

[0021] The product was tested and found to have a molecular weight (Mw) of 62,000, residual MA% monomer: 20 ppm, platinum cobalt chromaticity: 47, calcium carbonate dispersibility: 440 mg / g, and calcium chelate dispersibility: 550 mg / g. Comparative Example 2

[0022] The preparation method of the maleic acid-acrylic acid copolymer of this comparative example comprises the following steps: Step 1: Add 105g of pure water to a four-necked round-bottom flask, and mix copper sulfate pentahydrate and ferrous sulfate heptahydrate at a ratio of 0.0016 mol (molar ratio of Fe 2+ :Cu 2+ =1:1) was dissolved in 5g pure water to prepare a composite catalyst solution, which was then added to a four-necked flask; Step 2: Weigh 90g of maleic anhydride solid, add it to 192.6g of pure water, place in a water bath at 80°C, keep warm for 30 minutes, and after the hydrolysis is completed, cool to room temperature to prepare a maleic acid monomer solution; Step 3: Weigh 210 g of acrylic acid, add 20 g of pure water, and prepare an acrylic acid monomer solution; Step 4: Dissolve 1.5g VA-044 in 20g pure water to prepare the main initiator; Step 5: Weigh 50g of 25% hydrogen peroxide as a secondary initiator; Step 6: Start stirring, raise the temperature of the water bath to 55°C, and simultaneously add the primary initiator, secondary initiator, maleic acid monomer solution and acrylic acid monomer solution dropwise for 3 hours, maintain the reaction temperature at 55-60°C, and keep warm for 30 minutes after the primary initiator, secondary initiator, acrylic acid monomer solution and maleic acid monomer solution are added dropwise; Step 7: Cool down to below 45°C, add 342.5 g of 50% by mass sodium hydroxide solution to obtain a maleic acid-acrylic acid copolymer salt solution with a mass fraction of about 40%.

[0023] The product was tested and found to have a molecular weight (Mw) of 68,000, residual MA% monomer: 100 ppm, platinum cobalt chromaticity: 49, calcium carbonate dispersibility: 390 mg / g, and calcium chelate dispersibility: 478 mg / g. Comparative Example 3

[0024] The preparation method of the maleic acid-acrylic acid copolymer of this comparative example comprises the following steps: Step 1: Add 105 g of pure water to a four-necked round-bottom flask, dissolve 0.0016 mol of ferrous sulfate heptahydrate in 5 g of pure water, prepare a catalyst, and add it to the four-necked flask; Step 2: Weigh 90g of maleic anhydride solid, add it to 192.6g of pure water, place in a water bath at 80°C, keep warm for 30 minutes, and after the hydrolysis is completed, cool to room temperature to prepare a maleic acid monomer solution; Step 3: Weigh 210 g of acrylic acid, add 20 g of pure water, and prepare an acrylic acid monomer solution; Step 4: Dissolve 1.5g VA-044 in 20g pure water to prepare the main initiator; Step 5: Weigh 20g of 25% hydrogen peroxide as a secondary initiator; Step 6: Start stirring, heat the water bath to 55°C, and simultaneously drop the primary initiator, secondary initiator, maleate monomer solution and acrylic acid monomer solution. The dropwise addition time is 3 hours, and the reaction temperature is maintained at 55-60°C until the maleate monomer solution is added dropwise. Step 7: Continue to drop the main initiator, secondary initiator and acrylic acid monomer solution and complete the dropwise addition within 1 hour; Step 8: After all the additions are completed, keep the temperature for 30 minutes, cool down to below 45°C, add 342.5 g of 50% by mass sodium hydroxide solution, and obtain a maleic anhydride-acrylic acid copolymer salt solution with a mass fraction of about 40%.

[0025] The product was tested and found to have a molecular weight (Mw) of 63,000, residual MA% monomer of 74 ppm, platinum cobalt chromaticity of 55, calcium carbonate dispersibility of 401 mg / g, and calcium chelate dispersibility of 497 mg / g. Comparative Example 4

[0026] The preparation method of the maleic acid-acrylic acid copolymer of this comparative example comprises the following steps: Step 1: Add 105g of pure water to a four-necked round-bottom flask, and mix copper sulfate pentahydrate and ferrous sulfate heptahydrate at a ratio of 0.0016 mol (molar ratio of Fe 2+ :Cu 2+ =1:1) was dissolved in 5g pure water to prepare a composite catalyst solution, which was then added to a four-necked flask; Step 2: Weigh 90g of maleic anhydride solid, add it to 192.6g of pure water, place in a water bath at 80°C, keep warm for 30 minutes, and after the hydrolysis is completed, cool to room temperature to prepare a maleic acid monomer solution; Step 3: Weigh 210 g of acrylic acid, add 20 g of pure water, and prepare an acrylic acid monomer solution; Step 4: Weigh 50g of 25% hydrogen peroxide as an initiator; Step 5: Start stirring, raise the temperature of the water bath to 55°C, and simultaneously add the initiator, maleic acid monomer solution and acrylic acid monomer solution dropwise for 4 hours, maintain the reaction temperature at 55-60°C, and complete the addition of the maleate monomer solution; Step 6: After all the additions are completed, keep the temperature for 30 minutes, cool down to below 45°C, add 342.5 g of 50% by mass sodium hydroxide solution, and obtain a maleic anhydride-acrylic acid copolymer salt solution with a mass fraction of about 40%.

[0027] The product was tested and found to have a molecular weight (Mw) of 66,000, residual MA% monomer: 200 ppm, platinum cobalt chromaticity: 45, calcium carbonate dispersibility: 350 mg / g, and calcium chelate dispersibility: 370 mg / g.

[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a maleic acid-acrylic acid copolymer, characterized in that: The preparation method comprises the following steps: Step (1), preparing a composite catalyst solution using copper sulfate pentahydrate and ferrous sulfate heptahydrate; Step (2), respectively preparing an aqueous solution of an azo initiator as a main initiator and an aqueous solution of hydrogen peroxide as a secondary initiator; Step (3), preparing a maleic acid aqueous solution, referred to as monomer a; preparing an acrylic acid aqueous solution, referred to as monomer b; Step (4), adding pure water into a four-necked flask, then adding the composite catalyst solution, introducing nitrogen protection, heating the water bath to 55°C, starting stirring, and then simultaneously adding the primary initiator, secondary initiator, monomer a, and monomer b dropwise, and controlling the temperature at 55°C-60°C during the process; Step (5), after the addition of monomer a is completed, the main initiator, the secondary initiator and the monomer b are continued to be added dropwise, the time is controlled within 1 hour, and the temperature is maintained at 55-60°C. After all the additions are completed, the temperature is kept for 0.5-1 hour, and the temperature is lowered to obtain the maleic acid-acrylic acid copolymer aqueous solution.

2. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: In the step (1), the mass fraction of copper sulfate in the composite catalyst solution is 1%-10%, and the mass fraction of ferrous sulfate is 1%-10%.

3. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: In the step (1), the molar ratio of copper sulfate to ferrous sulfate in the composite catalyst is 0.25-2.

4. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: The main initiator azo initiator in step (2) is preferably a water-soluble azo initiator, specifically azobisisobutylamidine hydrochloride and / or azobisisobutylimidazoline hydrochloride, but an oil-soluble azo initiator or amphoteric azo initiator may also be used, such as azobisisobutylonitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azoisobutylcyanamide, and the like, but not limited thereto.

5. The method for preparing the maleic acid-acrylic acid copolymer according to claim 4, characterized in that: When the main initiator azo initiator is a mixture of azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride, the mass ratio thereof is 0.25-1.

6. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: The mass fraction of the main initiator azo initiator aqueous solution in step (2) is 2%-25%, preferably 5%-20%.

7. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: The mass fraction of the secondary initiator hydrogen peroxide aqueous solution in step (2) is 25%.

8. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: The maleic acid aqueous solution in step (3) is prepared by adding a certain amount of water to solid maleic anhydride and hydrolyzing it into a maleic acid aqueous solution.

9. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: In the step (5), the mass fraction of the acrylic acid aqueous solution is 90%-95%.

10. The method for preparing the maleic acid-acrylic acid copolymer according to claim 1, characterized in that: In the step (5), the molar ratio of maleic acid: acrylic acid: composite catalyst: azo initiator: hydrogen peroxide is 1: 1.0-3.6: 0.001-0.0018: 0.001-0.008: 0.3-0.7.

Citation Information

Cited By

  • A process for the preparation of MA / AA

    CN122978355A